Impact of implementing five-level triage system on patients outcomes and resource utilization in the emergency department of Alexandria main university hospital - Ahmed Abdel Fattah Sabry; Wael Nabil Abdel Salam; Mohammed Mostafa Abdel Salam; Khaled Salah Moustafa; Eman Mohamed Gaber; Bassem Nashaat Beshey (Egyptian Journal of Anaesthesia, 2023)
ABSTRACTObjective To investigate impact of five-level triage system on Emergency Department (ED) patients’ outcome and resources’ utilization.Design A comparative observational study (pre-/post-intervention).Setting ED of Alexandria Main University Hospital.Patients All trauma patients and adult emergencies presented to ED from 1st of September 2021 to 31st of May 2022. Patients who were discharged or left against medical advice were excluded.Methods Five-level triage was implemented in 1st of December 2021 using Australasian Triage Scale. Primary outcome was ED mortality, while secondary outcomes were resources’ utilization and ED length of stay (LOS). Multivariate logistic regression model for predictors of ED mortality was used.Results Totally, 9766 and 22,936 patients were subjected to three- and five-level triaging, respectively. ED mortality dropped from 5.26% to 1.46%. All resources including human factors were less utilized. ED LOS has declined from 170.1 ± 88.7 to 72.00 ± 109.8 min. All changes were statistically significant, p < 0.05. Significant predictors of ED mortality were three-level triaging, medical emergencies, initial code-1, time-to-clinical decision > 60 min, >5 differential diagnoses, more interventions, and longer ED LOS with different Odds ratios.Conclusion Five-level triaging reduced rates of mis-triaging, ED mortality, resources’ utilization, and ED LOS.